2008
DOI: 10.1152/ajpcell.90633.2007
|View full text |Cite
|
Sign up to set email alerts
|

Attenuation of retinal endothelial cell migration and capillary morphogenesis in the absence of bcl-2

Abstract: Kondo S, Tang Y, Scheef EA, Sheibani N, Sorenson CM. Attenuation of retinal endothelial cell migration and capillary morphogenesis in the absence of bcl-2.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
31
0

Year Published

2009
2009
2021
2021

Publication Types

Select...
10

Relationship

3
7

Authors

Journals

citations
Cited by 23 publications
(33 citation statements)
references
References 48 publications
2
31
0
Order By: Relevance
“…7C. Previous studies from our laboratories indicated that optimal endothelial cell migration is essential for capillary morphogenesis in vitro (4,7,14,29). Next, we determined whether decreasing eNOS expression restored capillary morphogenesis.…”
Section: Akita/ϩ Kidney Endothelial Cells Demonstrated Similar Levelsmentioning
confidence: 98%
“…7C. Previous studies from our laboratories indicated that optimal endothelial cell migration is essential for capillary morphogenesis in vitro (4,7,14,29). Next, we determined whether decreasing eNOS expression restored capillary morphogenesis.…”
Section: Akita/ϩ Kidney Endothelial Cells Demonstrated Similar Levelsmentioning
confidence: 98%
“…32 Loss of BCL2 was reported to inhibit migration of retinal endothelial cells, while enhancing cell adhesion and the motility of ureteric bud cells. 33,34 The cell type and context specific basis as to why different type of cells display different effects or even paradoxical opposite effects are not clear. In addition, distinct BCL2 expression level profiles of different cell type may dampen the BCL2 effect or even reverse its functions.…”
Section: Bcl2 Enhances Actin Polymerizationmentioning
confidence: 99%
“…We next determined the rate of apoptosis in TSP1 ϩ/ϩ and TSP1 Ϫ/Ϫ PCs in the presence or absence of 5-fluorouracil (1 mM), as previously described (23). We observed no significant differences in the rates of apoptosis in these cells (TSP1 ϩ/ϩ PCs: 1.2 Ϯ 0.09% vs. TSP1 Ϫ/Ϫ PCs: 1.4 Ϯ 0.12%, n ϭ 5, P Ͼ 0.05).…”
Section: Isolation Of Mouse Retinal Pcsmentioning
confidence: 99%